Die »offene« Mariologie Karl Rahners - Hartmann, Stefan (Zeitschrift für katholische Theologie, 2010)
Even though Karl Rahner had a strong interest in Mariology and wrote numerous studies on the topic, it has been neglected, and sometimes seriously misunderstood, in the reception of Rahner. Since the completion of the volume on Mariology in Rahner's Complete Works an evaluation of Rahner on Mariology is now possible and begun here.